A flame retardant insulating aerogel for overhead bare wires of power distribution grid and a preparation method thereof

By applying a flame-retardant insulating aerogel composed of cellulose-polyimide aerogel, graphene oxide, ammonium polyphosphate and boron nitride on the overhead bare wire of the power distribution grid, the wire insulation coating in the prior art is solved. The problem of the layer being unable to retardant, low strength and strong water absorption has achieved efficient insulation and flame retardant performance, ensuring reliable operation of the wire in bad weather.

CN118459840BActive Publication Date: 2025-02-11STATE GRID SHANDONG ELECTRIC POWER CO TANCHENG COUNTY POWER SUPPLY CO
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410573437.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2025-02-11
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

The insulating coating of existing power grid distribution overhead bare wires cannot effectively retardant flame, has low strength and strong water absorption, making it difficult to ensure reliable operation in bad weather.

Method used

A flame-retardant insulated aerogel consisting of cellulose-polyimide aerogel, graphene oxide, ammonium polyphosphate and boron nitride, and is prepared by atomizing spraying and freeze-drying to form a three-dimensional fiber. Skeleton structure to improve the insulation and flame retardant properties of the wire.

Benefits of technology

This aerogel has low thermal conductivity, excellent flame retardant properties and high thermal stability. It can maintain reliable operation of the conductors in severe weather such as lightning, salt spray, and freezing, and release a small amount of smoke during combustion, which has good fire resistance performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004831631460000091
    Figure BDA0004831631460000091
Patent Text Reader

Abstract

The present invention specifically relates to a flame retardant insulating aerogel applied to overhead bare conductors of power grid distribution and a preparation method thereof, belonging to the technical field of cable insulation materials. The present invention provides a preparation method of a flame retardant insulating aerogel applied to overhead bare conductors of power grid distribution, composite polyimide and cellulose aerogel, add graphene oxide, boron nitride and ammonium polyphosphate, and adopt atomization spraying to prepare a flame retardant insulating aerogel with low water absorption. The present invention is to solve the problems in the prior art that the insulating coating of overhead bare conductors of power grid distribution is not flame retardant, has low strength and water absorption. The flame retardant insulating aerogel applied to overhead bare conductors of power grid distribution provided by the present invention has both flame retardant and insulating effects, is light in weight but high in strength, and can still ensure reliable operation under the influence of severe weather such as lightning, salt spray, and freezing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to a flame retardant insulating aerogel applied to overhead bare wires of power grid distribution and a preparation method thereof, belonging to the technical field of cable insulation materials. Background Art

[0002] Overhead bare conductors for power grid distribution are a traditional way of power transmission. Their basic structure is made of highly conductive metals such as copper or aluminum, without outer insulation materials, and are directly exposed to the air for power transmission. This type of conductor is widely used due to its simple manufacturing and relatively low cost, especially in remote areas and in the early construction of power networks. Overhead bare conductors are mainly used in medium and low voltage distribution systems, especially high-voltage transmission lines of 10kV and above, relying on sufficient air gaps as electrical insulation media to the ground and between phases.

[0003] Overhead bare wires are commonly found in areas with open terrain, moderate humidity and less pollution, as well as areas that are not easily affected by severe weather such as lightning, salt spray, and freezing. However, in the process of urbanization, with the increase in building density, lush trees, increased environmental pollution, and the increase in requirements for power supply reliability and safety, the application of overhead bare wires has gradually exposed many problems. For example, bare wires are susceptible to environmental erosion, especially in coastal salt spray areas. The corrosion of the wires will lead to increased resistance and decreased mechanical strength, thus causing short circuit grounding, broken wires and other faults. In addition, bare wires are also susceptible to collisions with external objects, increasing the risk of electric shock.

[0004] In the face of the problem of bare conductors being uninsulated, the power engineering field has developed a variety of solutions and technologies. One of the methods is to insulate the original bare conductors. These conductors are wrapped with a layer of high-quality insulating materials such as polyvinyl chloride, cross-linked polyethylene or other high-performance polymers on the original metal core to enhance the conductor's ability to resist environmental corrosion and reduce the risk of short circuits. In addition, in order to improve the insulation performance of overhead bare conductors without replacing the entire line, there are also attempts to use insulating coatings for surface treatment. However, although conventional insulating coatings can isolate moisture and air to a certain extent and prevent wire corrosion, it is difficult to fully meet the standards of electrical insulation, and most coatings do not have good flame retardant properties. Once the line is overheated or on fire, non-flame retardant coatings cannot effectively prevent the spread of the fire. For example, CN112185628B discloses a high-temperature insulated wire semi-finished product and a preparation method thereof and a high-temperature insulated wire. The high-temperature insulated wire semi-finished product includes a wire core and a sol-gel composite coating coated on the periphery of the wire core. The sol-gel composite coating includes a polyvinyl alcohol-modified gel matrix and an inorganic filler dispersed in the polyvinyl alcohol-modified gel matrix. However, the method disclosed in the patent requires that the shape of the wire must be determined before the composite coating, because the coating needs to be sintered at a high temperature to be transformed into a ceramic insulating layer, which greatly limits the use conditions and cannot be flexibly applied.

[0005] As a new type of lightweight porous material, aerogel has attracted the attention of the power industry with its extremely low density, excellent thermal insulation performance and high specific surface area. However, aerogel also has the problems of low strength, flame retardancy, strong water absorption, and cannot be used in severe weather such as rain and snow. CN220305994U discloses a flame retardant insulated sheathless wire and cable, wherein a flame retardant heat insulation layer is provided on the outside of the cable core, an insulating sleeve is provided on the outside of the flame retardant heat insulation layer, and a plurality of filling grooves are penetrated at one end of the insulating sleeve, and the filling grooves are filled with aerogel, and the flame retardant heat insulation layer is a rock wool layer. It can be seen that in the disclosed technical solution, aerogel only bears the insulation function, and the flame retardant function is achieved by setting a rock wool layer. Such a structure is complicated, a single layer has only one function, and the manufacturing cost is high and the steps are complicated. Summary of the invention

[0006] In order to solve the problems in the prior art that the insulating coating of overhead bare wires of power grid distribution is not flame retardant, has low strength and is water absorbent, the present invention provides a flame retardant insulating aerogel applied to overhead bare wires of power grid distribution and a preparation method thereof. The aerogel has both flame retardant and insulating effects, is light in weight but high in strength, and can still ensure reliable operation under the influence of severe weather such as lightning, salt spray, and freezing.

[0007] The present invention provides a method for preparing a flame-retardant insulating aerogel applied to overhead bare wires of power grid distribution, comprising the following steps:

[0008] (1) adding a water-soluble diamine to water, stirring to dissolve, then adding a non-nucleophilic amine, and then adding a dianhydride, stirring to react, to obtain a polyamic acid aqueous solution;

[0009] (2) adding hexagonal boron nitride powder to a mixed solvent of isopropanol and deionized water, subjecting the solution to ultrasonic treatment, and then centrifuging the solution using a centrifuge, and taking the supernatant after centrifugation to obtain a boron nitride nanosheet dispersion;

[0010] (3) adding the polyamic acid aqueous solution obtained in step (1), the boron nitride nanosheet dispersion obtained in step (2), ammonium polyphosphate, and graphene oxide to the nanocellulose aqueous suspension, stirring and mixing, and then performing ultrasonic treatment;

[0011] (4) spraying the mixture obtained in step (3) into a cooling mold by atomization, and drying it using a freeze dryer to obtain an aerogel precursor;

[0012] (5) thermal imidization of the aerogel precursor obtained in step (4) in a tubular furnace to obtain the flame retardant insulating aerogel.

[0013] Furthermore, the water-soluble diamine in step (1) is one or more of ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine or 1,6-hexanediamine, the non-nucleophilic amine is one or more of triethylamine, trimethylamine, tri-n-butylamine, N-methylpyrrolidine, N-methylpiperidine, diisopropylethylamine, and the dianhydride is one or more of biphenyltetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, triphenylbis(ether)tetracarboxylic dianhydride, and hexafluorodianhydride.

[0014] Furthermore, in step (2), the volume ratio of isopropanol to deionized water in the mixed solvent is 1:1; the ultrasonic treatment time is 6-9 hours; the centrifuge speed in the centrifugal treatment is 8000-10000 rpm, and the centrifugation time is 15 min-25 min.

[0015] Furthermore, in step (3), the mass fraction of ammonium polyphosphate is 5-15%, the mass fraction of graphene oxide is 10-30%, the mass fraction of polyamic acid aqueous solution is 20%-30%, the mass fraction of boron nitride nanosheet dispersion is 5-10%, and the remainder is nanocellulose aqueous suspension.

[0016] Furthermore, in step (3), the concentration of the nanocellulose aqueous suspension is 1wt%-3wt%, and the nanocellulose is 400-500nm long and 5-10nm in diameter.

[0017] Furthermore, in step (3), the stirring and mixing time is 15-20 minutes, and the ultrasonic treatment time is 20-30 minutes.

[0018] Furthermore, in step (4), the atomization is performed through a 0.3 mm inner diameter steel nozzle at a constant pressure of 1.5 bar, the mold is cooled to -80°C to -90°C, the freeze-drying time is 26-48h, the freezing temperature is -50 to -90°C, and the vacuum degree is 0.025-0.1mbar.

[0019] Furthermore, the thermal imidization treatment process of step (5) is as follows: 120°C treatment time 0.5-2h, 150°C treatment time 0.5-2h, 200°C treatment time 0.5-2h, 250°C treatment time 2-4h.

[0020] Furthermore, the mold can be adjusted according to the size of the wire, and the manufactured aerogel can be directly sleeved on the periphery of the wire.

[0021] The beneficial effects of the present invention are:

[0022] (1) The present application uses cellulose-polyimide aerogel, combined with graphene oxide, ammonium polyphosphate and boron nitride to form the flame-retardant insulating aerogel for use in overhead bare wires of power distribution networks; the nanofibers used are entangled with each other, and a network structure can be formed even at very low concentrations. The present application adopts an atomization spray freezing method, and the prepared aerogel obtains a three-dimensional fibrous skeleton morphology. When sprayed onto the mold surface at -80°C, small droplets with a diameter of about tens of microns form a thin dispersion on the mold surface. The thinner sample layer has a higher cooling rate. Rapid cooling does not allow cellulose and polyimide to agglomerate. In the subsequent freeze-drying sublimation process, the strong hydrogen bonds formed between the hydroxyl groups on the adjacent cellulose surfaces maintain the structure, so that the aerogel presents a 3D-fibril skeleton morphology, and the pore wall thickness is smaller, and the air molecules are confined in pores with a smaller free path, which makes the flame-retardant insulating aerogel described in the present application have a very low thermal conductivity. In addition, nano boron nitride is added as a filler to the flame-retardant insulating aerogel described in the present application, so that the thermal conductivity of the material is further reduced.

[0023] (2) The flame-retardant insulating aerogel described in the present application also contains graphene oxide, boron nitride and ammonium polyphosphate. The inventors have found that ammonium polyphosphate can improve the thermal stability of the composite aerogel at high temperatures. Generally, the thermal stability of graphene oxide is similar to that of cellulose aerogel, but the freeze-drying method of ammonium polyphosphate combined with atomization spraying makes the aerogel have better thermal stability. In addition, the flame-retardant insulating aerogel described in the present application releases very little smoke during combustion, forms a thick carbon layer on the surface during the combustion process, and maintains its original shape after combustion. The shrinkage rate is also very small, and it has excellent flame retardancy.

[0024] (3) In view of the fact that cellulose aerogel in the prior art has strong water absorption and is difficult to be applied to bare wires, the inventors attempted to introduce composite aerogels. Generally, a single polyimide aerogel also has strong water absorption, and after absorbing water, it will cause irreversible damage to the structure of the aerogel itself and cannot be used again, and it cannot cope with abnormal weather such as rain and snow outdoors. However, the flame-retardant insulating aerogel prepared by the preparation method provided by the present invention does not have high water absorption. This may be because the rapid cooling through atomization spraying leads to the formation of strong hydrogen bonds between the hydroxyl groups on the surfaces of adjacent nanocelluloses, and when the polyimide is composited with the cellulose aerogel, the hydrophobic groups of the polyimide cover the hydroxyl surface of the cellulose, preventing water molecules from directly contacting the hydroxyl groups of the nanocellulose. DETAILED DESCRIPTION

[0025] The technical scheme of the present invention and its effects are further described below by specific examples. The following examples are only used to illustrate the content of the present invention and are not used to limit the protection scope of the present invention. Simple changes made to the present invention by applying the concept of the present invention are all within the scope of the protection claimed by the present invention.

[0026] The equipment used in the preparation method of the present invention can be well-known equipment in the art. The raw materials used in the present invention are commercially available unless otherwise specified. The nanocellulose is TEMPO oxidized nanocellulose produced by Nanjing Huikang Biotechnology Co., Ltd., and the graphene oxide is produced by Guangdong Innovation Materials.

[0027] Example 1

[0028] (1) 3.6 g of ethylenediamine was added to 50 ml of water, and after stirring to dissolve, 3.5 g of N-methylpyrrolidine was added, and then 16.8 g of 3,3',4,4'-biphenyltetracarboxylic dianhydride was added and stirred to react to obtain a polyamic acid aqueous solution;

[0029] (2) adding hexagonal boron nitride powder to a mixed solvent of isopropanol and deionized water in a volume ratio of 1:1, subjecting the solution to ultrasonic treatment for 7 hours, and then centrifuging it in a centrifuge at a speed of 8000 rpm for 20 minutes, and taking the supernatant after centrifugation to obtain a boron nitride nanosheet dispersion;

[0030] (3) Add the polyamic acid aqueous solution obtained in step (1), the boron nitride nanosheet dispersion obtained in step (2), ammonium polyphosphate, and graphene oxide to a nanocellulose aqueous suspension, wherein the nanocellulose is TEMPO-oxidized nanocellulose, the nanocellulose aqueous suspension concentration is 1wt%, the nanocellulose is 400-500nm long, 5-10nm in diameter, and has a carboxylate content of 1.1-1.5mmol / g. The mass fraction of the nanocellulose is 13.7%, the mass fraction of the polyamic acid is 68.2%, the mass fraction of the graphene oxide is 4.5%, the mass fraction of the ammonium polyphosphate is 6.8%, and the mass fraction of the boron nitride nanosheet is 6.8%. Stir and mix for 20min and then perform ultrasonic treatment for 30min;

[0031] (4) The mixture obtained in step (3) was sprayed through a 0.4 mm inner diameter steel nozzle at a constant pressure of 1.5 bar, the mold was cooled to -80°C, the freeze-drying time was 48 h, the freezing temperature was -90°C, and the vacuum degree was 0.1 mbar to obtain an aerogel precursor.

[0032] (5) The aerogel precursor obtained in step (4) is subjected to thermal imidization in a tubular furnace, and is kept warm at a temperature of 100-110° C. for 0.5-1 h, then kept warm at a temperature of 190-200° C. for 0.5-1 h, then kept warm at a temperature of 270-280° C. for 0.5-1 h, and finally kept warm at a temperature of 340-350° C. for 1.5 h to 2.5 h to obtain the flame retardant insulating aerogel.

[0033] Example 2

[0034] (1) 5.2 g of 1,4-butanediamine was added to water, and after stirring to dissolve, 7.8 g of diisopropylethylamine was added, and then 19 g of benzophenonetetracarboxylic dianhydride was added, and the mixture was stirred to react to obtain a polyamic acid aqueous solution;

[0035] (2) adding hexagonal boron nitride powder to a mixed solvent of isopropanol and deionized water in a volume ratio of 1:2, subjecting the solution to ultrasonic treatment for 6 hours, and then centrifuging it in a centrifuge at a speed of 8000 rpm for 25 minutes, and taking the supernatant after centrifugation to obtain a boron nitride nanosheet dispersion;

[0036] (3) Add the polyamic acid aqueous solution obtained in step (1), the boron nitride nanosheet dispersion obtained in step (2), ammonium polyphosphate, and graphene oxide to a nanocellulose aqueous suspension, wherein the nanocellulose is TEMPO-oxidized nanocellulose, the nanocellulose aqueous suspension concentration is 3wt%, the nanocellulose is 400-500nm long, 5-10nm in diameter, and the carboxylate content is 1.1-1.5mmol / g. The mass fraction of the nanocellulose is 17.3%, the mass fraction of the polyamic acid is 51.8%, the mass fraction of the graphene oxide is 10.3%, the mass fraction of the ammonium polyphosphate is 17.2%, and the mass fraction of the boron nitride nanosheet is 3.4%. Stir and mix for 20min and then perform ultrasonic treatment for 30min;

[0037] (4) The mixture obtained in step (3) was sprayed through a 0.3 mm inner diameter steel nozzle at a constant pressure of 1.9 bar, the mold was cooled to -90°C, the freeze-drying time was 26 h, the freezing temperature was -90°C, and the vacuum degree was 0.1 mbar to obtain an aerogel precursor.

[0038] (5) The aerogel precursor obtained in step (4) is subjected to thermal imidization in a tubular furnace, and is kept warm at a temperature of 100-110° C. for 0.5-1 h, then kept warm at a temperature of 190-200° C. for 0.5-1 h, then kept warm at a temperature of 270-280° C. for 0.5-1 h, and finally kept warm at a temperature of 340-350° C. for 1.5 h to 2.5 h to obtain the flame retardant insulating aerogel.

[0039] Example 3

[0040] (1) 6 g of 1,6-hexanediamine was added to water, and after stirring to dissolve, 1.8 g of trimethylamine was added, and then 21.7 g of triphenyl bis(ether) tetracarboxylic dianhydride was added, and the mixture was stirred to react to obtain a polyamic acid aqueous solution;

[0041] (2) adding hexagonal boron nitride powder to a mixed solvent of isopropanol and deionized water in a volume ratio of 1:2, subjecting the solution to ultrasonic treatment for 6 hours, and then centrifuging it in a centrifuge at a speed of 8000 rpm for 25 minutes, and taking the supernatant after centrifugation to obtain a boron nitride nanosheet dispersion;

[0042] (3) Add the polyamic acid aqueous solution obtained in step (1), the boron nitride nanosheet dispersion obtained in step (2), ammonium polyphosphate, and graphene oxide to the nanocellulose aqueous suspension, wherein the nanocellulose is TEMPO-oxidized nanocellulose, the nanocellulose aqueous suspension concentration is 3wt%, the nanocellulose is 400-500nm long, 5-10nm in diameter, and the carboxylate content is 1.1-1.5mmol / g. The mass fraction of nanocellulose is 16.4%, the mass fraction of polyamic acid is 61.8%, the mass fraction of graphene oxide is 12.3%, the mass fraction of ammonium polyphosphate is 5.4%, and the mass fraction of boron nitride nanosheet is 4.1%. Stir and mix for 20min and then perform ultrasonic treatment for 30min;

[0043] (4) The mixture obtained in step (3) was sprayed through a 0.3 mm inner diameter steel nozzle at a constant pressure of 1.7 bar, the mold was cooled to -85°C, the freeze-drying time was 44 h, the freezing temperature was -50°C, and the vacuum degree was 0.1 mbar to obtain an aerogel precursor.

[0044] (5) The aerogel precursor obtained in step (4) is subjected to thermal imidization in a tubular furnace, and is kept warm at a temperature of 100-110° C. for 0.5-1 h, then kept warm at a temperature of 190-200° C. for 0.5-1 h, then kept warm at a temperature of 270-280° C. for 0.5-1 h, and finally kept warm at a temperature of 340-350° C. for 1.5 h to 2.5 h to obtain the flame retardant insulating aerogel.

[0045] Comparative Example 1

[0046] The freeze drying step was changed to direct introduction into the mold for freezing, and the rest was the same as Example 1.

[0047] Comparative Example 2

[0048] Graphene and ammonium polyphosphate were not added, and the rest was the same as in Example 1.

[0049] Comparative Example 3

[0050] The mass fraction of nanocellulose is 33.7%, the mass fraction of polyamic acid is 48.2%, the mass fraction of graphene oxide is 4.5%, the mass fraction of ammonium polyphosphate is 6.8%, the mass fraction of boron nitride nanosheets is 6.8%, and the rest is the same as in Example 1.

[0051] The flame retardant insulating aerogels prepared according to the above examples and comparative examples were subjected to performance tests:

[0052]

[0053] The water absorption test: weigh the sample and immerse the sample completely in water in a closed tank for 24 hours, then take the sample out of the water, wipe off the surface water of the aerogel, and then weigh the sample again.

[0054] Flame retardant performance test: A combustion experiment was conducted to observe the flammable behavior of the aerogel. A rectangular aerogel sample with a size of 0.8 cm × 0.8 cm × 1.8 cm was clamped on a steel frame and ignited longitudinally with an alcohol lamp.

Claims

1. A method for preparing a flame retardant insulating aerogel for use in overhead bare wires of power distribution networks, characterized in that The following steps are involved: (1) adding a water-soluble diamine to water, stirring to dissolve, adding a non-nucleophilic amine, and then adding a dianhydride, stirring to react, to obtain a polyamic acid aqueous solution, wherein the molar ratio of the diamine, the non-nucleophilic amine and the dianhydride is 1:0.5~1:0.9~1, the water-soluble diamine is one or more of ethylenediamine, 1,3-propylenediamine, 1,4-butylenediamine, 1,5-pentanediamine or 1,6-hexanediamine, the non-nucleophilic amine is one or more of triethylamine, trimethylamine, tri-n-butylamine, N-methylpyrrolidine, N-methylpiperidine, and diisopropylethylamine, and the dianhydride is one or more of biphenyltetracarboxylic dianhydride, benzophenonetetracarboxylic dianhydride, triphenylbisethertetracarboxylic dianhydride, and hexafluorodianhydride; (2) adding hexagonal boron nitride powder to a mixed solvent of isopropanol and deionized water, subjecting the solution to ultrasonic treatment, and then centrifuging the solution using a centrifuge, and taking the supernatant after centrifugation to obtain a boron nitride nanosheet dispersion; (3) adding the polyamic acid aqueous solution obtained in step (1), the boron nitride nanosheet dispersion obtained in step (2), ammonium polyphosphate, and graphene oxide to the nanocellulose aqueous suspension, wherein the mass ratio of nanocellulose to polyamic acid and graphene oxide is 3-5:15:1-3, the mass ratio of boron nitride nanosheets to nanocellulose is 1:2-5, and the mass ratio of ammonium polyphosphate to nanocellulose is 1:1-3, stirring and mixing, and then performing ultrasonic treatment; (4) spraying the mixture obtained in step (3) into a cooling mold by atomization, the atomization is performed through a 0.2-0.4 mm inner diameter steel nozzle, and the atomization is performed at a constant pressure of 1.5-1.9 bar. The mold is cooled to -80°C to -90°C, and then dried using a freeze dryer to obtain an aerogel precursor. The freeze drying time is 26-48 hours, the freezing temperature is -50-90°C, and the vacuum degree is 0.025-0.1 mbar; (5) The aerogel precursor obtained in step (4) is subjected to thermal imidization in a tubular furnace to obtain the flame retardant insulating aerogel.

2. The method for preparing the flame-retardant insulating aerogel for use in overhead bare wires of power distribution networks according to claim 1, characterized in that: In step (2), the volume ratio of isopropanol to deionized water in the mixed solvent is 1:1-2; the ultrasonic treatment time is 6-9 hours; the centrifuge speed in the centrifugal treatment is 8000-10000 rpm, and the centrifugation time is 15-25 minutes.

3. The method for preparing the flame-retardant insulating aerogel for use in overhead bare wires of power distribution networks according to claim 1, characterized in that: The nanocellulose in step (3) is TEMPO-oxidized nanocellulose, the concentration of the nanocellulose aqueous suspension is 1-3 wt %, the nanocellulose is 400-500 nm long, 5-10 nm in diameter, and has a carboxylate content of 1.1-1.5 mmol / g.

4. The method for preparing the flame-retardant insulating aerogel for use in overhead bare wires of power distribution networks according to claim 1, characterized in that: The stirring and mixing time in step (3) is 15 to 20 minutes, and the ultrasonic treatment time is 20 to 30 minutes.

5. The method for preparing the flame-retardant insulating aerogel for use in overhead bare wires of power distribution networks according to claim 1, characterized in that: The thermal imidization treatment process of step (5) is to keep the temperature at 100-110°C for 0.5-1h, then keep the temperature at 190-200°C for 0.5-1h, then keep the temperature at 270-280°C for 0.5-1h, and finally keep the temperature at 340-350°C for 1.5h-2.5h.

6. A flame retardant insulating aerogel used for overhead bare wires of power distribution grids, characterized in that: Prepared by the preparation method according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • High-temperature insulated wire semi-finished product and its preparation method and high-temperature insulated wire

    CN112185628B

  • Flame-retardant insulating sheath-free wire cable

    CN220305994U

  • Method for preparing polyimide-graphene composite aerogel through in-situ polymerization

    CN106750290A

  • Polyimide aerogel and preparation method thereof

    CN109912833A